Highly multiplex and sensitive SNP genotyping method using a three‐color fluorescence‐labeled ligase detection reaction coupled with conformation‐sensitive CE. Issue 3 (22nd November 2016) - Choi, Woong; Jung, Gyoo Yeol
Abstract : For the development of clinically useful genotyping methods for SNPs, accuracy, simplicity, sensitivity, and cost‐effectiveness are the most important criteria. Among the methods currently being developed for SNP genotyping technology, the ligation‐dependent method is considered the simplest for clinical diagnosis. However, sensitivity is not guaranteed by the ligation reaction alone, and analysis of multiple targets is limited by the detection method. Although CE is an attractive alternative to error‐prone hybridization‐based detection, the multiplex assay process is complicated because of the size‐based DNA separation principle. In this study, we employed the ligase detection reaction coupled with high‐resolution CE‐SSCP to develop an accurate, sensitive, and simple multiplex genotyping method. Ligase detection reaction could amplify ligated products through recurrence of denaturation and ligation reaction, and SSCP could separate these products according to each different structure conformation without size variation. Thus, simple and sensitive SNP analysis can be performed using this method involving the use of similar‐sized probes, without complex probe design steps. We found that this method could not only accurately discriminate base mismatches but also quantitatively detect 37 SNPs of the tp53 gene, which are used as targets in multiplex analysis, using three‐color fluorescence‐labeled probes.